Attitudes of the Secondary Level Dhimal Students towards Mathematics and its Relationship with their Achievement - Neupane, Kamal Prasad (New Journey, 2024)
This research work mainly explores the attitudes of 50 Dhimal students towards Mathematics subject. Mathematics is a major subject to study for the students form Primary level to Master level and above. So it has been given a high priority in school curriculum. In such context, this research paper focuses on the ideas and attitudes of the students of secondary level from a marginalized group of Dhimal people. The main problem of the study was to explore the attitudes of the Dhimal students towards mathematics. The objectives of the study were to find out the attitude and achievement of Dhimal students’ towards the school mathematics. The nature of this study was of survey type and based on quantitative data. The researcher collected the data about the attitude of Dhimal students towards mathematics and their achievement as sample from Radhika S. School and Araniko S. School in Urlabari, Morang. It was found that the secondary level Dhimal students had positive attitude towards mathematics.